PENGABDIAN PADA MASYARAKAT MELALUI KULIAH KERJA MAHASISWA (KKM) DI KELURAHAN KEPUH KECAMATAN CIWANDAN KOTA CILEGON - Hendrawati, Sulkiah; Fatari, Fatari; Sumarsih, Rani Sri; Febrianto, Muhamad Rizki; Gupron, Akhmad; Yulianti, Evi; Abro, Fikri; Pratama, Mochamad Jodi (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
Community service through Student Work Lectures conducted by group 46 students in the Kepuh sub-district, Ciwandan sub-district by providing community assistance in social, economic, health, educational, legal and religious aspects as well as appropriate technology. Student Work Lectures are field activities carried out by students over a certain period of time and are an implementation of the Tridharma of higher education. The method for student work study activities currently focuses more on implementing work programs that have been prepared systematically. Carried out by Group 46 Students and Field Supervising Lecturers and Field Supervising Lecturers by going directly to the field to visit the community and the data sources needed to ask for information through direct interviews both personally and organizationally or data sources obtained through sub-district offices or sub-district offices. subdistrict. Results and Discussion; forming work programs, implementing work programs, implementing work programs and the role of Field Supervisors and Field Assistant Lecturers. In conclusion; there is an understanding related to digital marketing specifically for entrepreneurship, there is awareness about healthy living, there is legal awareness and an understanding of the importance of education. The creation of outcomes as a result of Community Service